Decadal-scale changes in the effect of the QBO on the northern stratospheric polar vortex - Lu, H; Baldwin, M; Gray, L; Jarvis, M (2008)
This study documents decadal-scale changes in the Holton and Tan (HT) relationship, i.e., the influence of the lower stratospheric equatorial quasi-biennial oscillation (QBO) on the northern hemisphere (NH) extratropical. circulation. Using a combination of ECMWF ERA-40 Reanalysis and Operational data from 1958-2006, we find that the Arctic stratosphere is indeed warmer under easterly QBO and colder under westerly QBO. During November to January, composite easterly minus westerly QBO signals in zonal wind extend from the lower stratosphere to the upper stratosphere and are centered at ∼5 hPa, 55-65°N with a magnitude of ∼10 m s-1. In temperature, the maximum signal is near ∼20-30 hPa at the pole with a magnitude of ∼4 K. During winter, the dominant feature is a poleward and downward transfer of wind and temperature anomalies from the midlatitude upper stratosphere to the high latitude lower stratosphere. For the first time, a statistically significant decadal scale change of the HT relationship during 1977-1997 is diagnosed. The main feature of the change is that the extratropical QBO signals reverse sign in late winter, resulting in fewer and delayed major stratospheric sudden warmings (SSWs), which occurred more often under westerly QBO. Consistent with earlier studies, it is found that the HT relationship is significantly stronger under solar minima overall, but the solar cycle does not appear to be the primary cause for the detected decadal-scale change. Possible mechanisms related to changes in planetary wave forcing are discussed. Copyright 2008 by the American Geophysical Union.